Organizing global supply chains: input cost shares and vertical integration - Berlingieri, Giuseppe; Pisch, Frank; Steinwender, Claudia (London, 2018)
"We study whether and how the technological importance of an input – measured by its cost share – is related to the decision of whether to “make” or “buy” that input. Using detailed French international trade data and an instrumental variable approach based on self-constructed IO tables, we show that French multinationals vertically integrate those inputs that have high cost shares. A stylized incomplete contracting model with both ex ante and ex post inefficiencies explains why: technologically more important inputs are “made” when transaction cost economics type forces (TCE; favoring integration) overpower property rights type forces (PRT; favouring outsourcing). Additional results related to the contracting environment and headquarters intensity consistent with our theoretical framework show that both TCE and PRT type forces are needed to fully explain the empirical patterns in the data "